First Principles Study of NaCl···A-B Type (A-B = Acceptor) Complexes - KC, Bimal; Parajuli, Rajendra (Journal of Institute of Science and Technology, 2025)
A first-principles study of NaCl•••A-B type (A-B =acceptor) complexes was performed using ab initio methods and the Atoms in Molecules (AIM) approach. We have considered ten different acceptors: C2H4, NH3, H2O, H2, HF, HNa, HLi, FNa, FLi, NaCl. This work reports whether these complexes form sodium bonds by examining sodium bond distances, bond angles, frequency shifts, binding energies, and topological parameters (electron density and Laplacian of electron density at sodium bond critical points). We calculated binding energies by correcting for both basis set superposition error and zero-point vibrational energies. Our findings reveal both red and blue shifts in the stretching frequency modes. The value of electron density and the value of the Laplacian of the electron density are consistent with earlier reports on sodium bonding. This study further shows that sodium bond distances are more closely related to ionic radii than to van der Waals radii, with notable differences compared to hydrogen bond radii. All these results provide the nature of sodium bonding, and its unique characteristics compared to other non-covalent interactions.